The gender gap in wage expectations: Do young women trade off higher wages for lower wage risk? - Vaishali Zambre (Deutsches Institut für Wirtschaftsforschung (DIW), 2018)
Several studies show that young women start with lower wage expectations than men, even before entering the labor market and that this partly translates into the actual gender wage gap through effects on educational choice and the formation of reservation wages. Building on the theoretical reasoning of compensating differentials proposing that the labor market compensates higher wage risk with higher wages, this study investigates whether the gender gap in wage expectations can be explained by individuals anticipating this form of risk compensation. Relying on a unique survey on German high school graduates in which we elicited information on the entire distribution of expected wages, this study documents that already at this early stage, female students expect to earn around 16% less than their male counterparts. At the same time, they expect lower wage risk as measured by the individual-specific dispersion in wage expectations. I decompose the gender gap into components attributable to socio-demographic factors, academic performance and skills, intended college major choice, career motives, personality traits, economic preferences, measures for students' confidence and expected wage risk. The results indicate that anticipated compensation for wage risk plays a major role in explaining the gender gap in wage expectations suggesting that females have lower wage expectations because they are willing to trade off higher wages for lower wage risk. The results of this study shed light on why young women make different choices regarding education and careers, thereby enhancing our understanding of the observed gender wage gap.
Keywords: I28; J18; D04; 330; wage expectations; gender gap; wage risk; risk compensation